2016
DOI: 10.4103/0976-3147.176196
|View full text |Cite
|
Sign up to set email alerts
|

Vascular malformations of central nervous system: A series from tertiary care hospital in South India

Abstract: Aims and Objectives:To describe clinicopathological features of surgically resected vascular malformations (VMs) of central nervous system (CNS).Materials and Methods:Histologically diagnosed cases of VMs of CNS during April 2010–April 2014 were included. Demographic data, clinical and radiological features were obtained. Hematoxylin and eosin slides were reviewed along with Verhoeff-Van Gieson (VVG), Masson's trichrome, periodic acid-Schiff, and Perls' stains. Morphologically, cavernomas and arteriovenous mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…7 In a study by Karri et al in south India, CCMs were found to be more common than the AVMs, accounting for 72% (36/50) of all VMs. 6…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 In a study by Karri et al in south India, CCMs were found to be more common than the AVMs, accounting for 72% (36/50) of all VMs. 6…”
Section: Discussionmentioning
confidence: 99%
“…We found only one other study that documented spectrum of 50 cases of VMs. 6 Most common VMs are AVMs and CCMs, with detection rates of approximately 1.1 and 0.6 per 100,000 adults per year. In our series, CCM were the most common VMs overall, AVMs being the most frequent amongst intracranial VMs and hemangiomas and AVF being most common in spine.…”
Section: Discussionmentioning
confidence: 99%
“…The main options for the management of AVM include conservative management with serial imaging and observation, microsurgical resection, endovascular embolization, and stereotactic radiosurgery. [5] The combined or staged therapy is also gaining popularity through multidisciplinary decision-making approaches.…”
Section: Cerebralmentioning
confidence: 99%
“…Most of cavernomas were found in cerebral hemispheres (66.7%), spinal cord (13.9%), brain stem (11.1%), and cerebellum (11.1%). [5] AVMs are abnormal complex tangles of blood vessels which cause numerous shunts between the arterial and venous systems. They frequently occur in the brain and to a lesser degree in the spinal cord.…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral cavernous malformations (CCMs) are hamartomas with endothelium-lined vascular chambers [ 1 , 2 ]. CCMs lack developed vascular structures like elastic lamina, smooth muscle, or tight junctions; have no interspersed brain parenchyma; and have a border of nonfunctioning glial tissue [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%